Interview with the winner of the national instrumentation prize - rmib, rmib (Revista Mexicana de Ingenieria Biomedica, 2018)
Convened by CONACYT and the Mexican Society of Physiological Sciences, this year an important event was held again within the National Congress of Physiological Sciences: THE BIOMEDICAL INSTRUMENTATION COMPETITION. Among many and valuable prototypes presented, the jury was unanimously voted in favor of the "Analogue Electrical Analog Signal Analyzer" "ASAE II"